2018
DOI: 10.1007/s11239-018-1652-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of anticoagulation clinics in the United States: an AC forum membership survey

Abstract: Many anticoagulation clinics have adapted their services to provide care for patients taking direct oral anticoagulants (DOAC) in addition to traditional warfarin management. Anticoagulation clinic scope of service and operations in this transitional environment have not been well described in the literature. A survey was conducted of United States-based Anticoagulation Forum members to inquire about anticoagulation clinic structure, function, and services provided. Survey responses are reported using summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
0
26
0
2
Order By: Relevance
“…The first theme to emerge from the interviews was that most providers were unaware of the services provided by the anticoagulation clinic for DOAC patients or the benefits of referral to the anticoagulation clinic (Table ). From the survey data, 83 of 159 (52.2%) of respondents indicated that their anticoagulation clinic provides care for DOAC patients, but the median estimated percent of their clinic made up of DOAC patients was 10% (IQR 5%‐30%) . There was no association between a clinic offering DOAC care and the clinic size (OR 1.013, 95% CI 0.993‐1.034, P = 0.191 for every 100 patients managed in the clinic).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The first theme to emerge from the interviews was that most providers were unaware of the services provided by the anticoagulation clinic for DOAC patients or the benefits of referral to the anticoagulation clinic (Table ). From the survey data, 83 of 159 (52.2%) of respondents indicated that their anticoagulation clinic provides care for DOAC patients, but the median estimated percent of their clinic made up of DOAC patients was 10% (IQR 5%‐30%) . There was no association between a clinic offering DOAC care and the clinic size (OR 1.013, 95% CI 0.993‐1.034, P = 0.191 for every 100 patients managed in the clinic).…”
Section: Resultsmentioning
confidence: 98%
“…The quantitative data was collected via an online survey of anticoagulation clinic providers (Online Appendix). Details have been published previously . Briefly, we invited all active members of the Anticoagulation Forum (a large peer organization of anticoagulation service providers in North America) to participate in an online survey.…”
Section: Methodsmentioning
confidence: 99%
“…A recent survey of anticoagulation clinics registered with the Anticoagulation Forum found that 90% of the patients being managed within AMS models were being managed for warfarin use. Although 50% of clinics surveyed reported incorporation of DOACs into their service, only 10% of patients managed are DOAC users, creating a gap between use and management services . While patients receiving DOACs do not require routine laboratory monitoring, they are still at high risk of drug‐related adverse events .…”
Section: Developing and Evaluating New Ams Models Including Doacsmentioning
confidence: 99%
“…In a recent survey of AMS registered with the Anticoagulation Forum, nearly 50% of clinics reported operating with a mixture of personnel (pharmacists, nurses, medical assistants, physician assistants). Approximately 70% of those clinics report utilizing pharmacists . Data derived from AMS evaluation primarily involve warfarin management.…”
mentioning
confidence: 99%
See 1 more Smart Citation